PERUBAHAN KARAKTERISTIK BEBERAPA SIFAT KIMIA TANAH DENGAN PEMBERIAN BIOCHAR DAN PUPUK KANDANG AYAM PADA TANAH ULTISOL - Bahri, Samsul; Budianta, Dedik; Munandar, Munandar (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2016)
Soil fertility absolute attention in order to get maximum results. Efforts to improve soil fertility them with chemical fertilizer, manure and agricultural waste utilization. Some chemical properties that may be indicators of soil fertility such as N-available, K-available and P-available. This study aims to look at the effect of biochar and chicken manure on the total-N, available P and K-are available. The method used in this research is experimental randomized block design (RAK) arranged as factorial, consisting of two treatment factors and repeated three times. The first factor is the provision of biochar (B) consisting of B0: control, B1: 0.25 tonnes / ha equivalent to 0.25 kg / m2, B2 5 ton / ha equivalent to 0.5 kg / m2 and B3: 10 ton / ha biochar is equivalent to 1 kg / m2. The second factor is the provision of chicken manure chicken (K) consists of four levels ie K0: Control, K1: 2.5 tons / ha is equivalent to 0.25 kg / m2, K2: 5 tonnes / ha equivalent to 0.5 kg / m2, and K3: 10 ton / ha equivalent to 1 kg / m2. In this study, there are 16 combinations of treatments, each treatment was repeated 3 times in order to get 48 units experimental observations summarized as follows: dose biochar significant effect on K- provided and no significant effect on N-total and P-available. Treatment of chicken manure is very significant effect on P-available and no real effect on total-N and K-are available.